2012
DOI: 10.1021/ma300964y
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh-Instability-Driven Morphology Transformation by Thermally Annealing Electrospun Polymer Fibers on Substrates

Abstract: Electrospinning has been widely used to prepare polymer fibers with diameters ranging from a few nanometers to micrometers. While most studies focus on controlling the sizes and morphologies of electrospun polymer fibers by changing electrospinning conditions, the effect of post-treatments such as thermal annealing on the properties of electrospun polymer fibers has been less studied. Here, we investigate the effect of thermal annealing on the morphology changes of electrospun polystyrene (PS) fibers on substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 29 publications
1
39
1
Order By: Relevance
“…As a result, the interfacial areas between the electrospun ABS fibers and the PMMA film decrease, reducing the interfacial energies. The result is consistent with our previous studies on annealing PS fibers on PMMA films …”
Section: Resultssupporting
confidence: 94%
“…As a result, the interfacial areas between the electrospun ABS fibers and the PMMA film decrease, reducing the interfacial energies. The result is consistent with our previous studies on annealing PS fibers on PMMA films …”
Section: Resultssupporting
confidence: 94%
“…For polymer fibers in contact with the substrate, wetting or dewetting on the substrate might occur after thermal annealing. Previously, we studied that electrospun PS fibers can wet the glass substrate after thermal annealing . We also found that a Rayleigh‐instability‐driven morphology transformation can be observed when the electrospun PS fibers are annealed on a PMMA‐coated substrate.…”
Section: Resultsmentioning
confidence: 84%
“…After thermal annealing, the values of WCAs of polymer fibers are close to those of bulk polymer films. Rayleigh‐instability‐type transformation of the electrospun fibers, however, is not observed in this system …”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although the morphologies and properties of electrospun polymer fibers have been extensively studied, the morphology transformation of electrospun fibers has been less investigated . Here, we develop a novel approach to anneal electrospun polymer fibers embedded in polymer films.…”
Section: Introductionmentioning
confidence: 99%